A three-dimensional lithiumophilic material, its preparation method and application

CN116259760BActive Publication Date: 2026-10-16NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111509249.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-10
Publication Date
2026-10-16
Estimated Expiration
2041-12-10

AI Technical Summary

Technical Problem

但是三维集流体是电子的良导体,在SEI膜破裂时仍无法抑制电子与电解液的反应,对锂金属的保护作用较小

Benefits of technology

[0031] The beneficial effects that this application can produce include:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116259760B_ABST
    Figure CN116259760B_ABST
Patent Text Reader

Abstract

The application provides a three-dimensional lithium-philic material preparation method and application. A solvent thermal reaction is used to form a uniform nanowire Nb2O5 protective structure in situ on the surface of a carbon paper current collector. The Nb2O5 modified carbon paper current collector has a large specific surface area, which is beneficial to the penetration of the liquid electrolyte in the electrode and improves the diffusion rate of lithium ions. The Nb2O5 uniformly wraps the carbon paper current collector, can inhibit the direct reaction of electrons and electrolyte, and plays a regulating role in the lithium metal deposition process. The current collector exhibits high rate performance and excellent cycle stability in the liquid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a method for preparing a three-dimensional lithiophilic material, and more particularly to a method for preparing and applying a three-dimensional current collector for a high-performance lithium metal anode, belonging to the field of electrochemical technology. Background Technology

[0002] The widespread use of lithium-ion batteries has solved the problem of redundant wiring in electronic devices. However, with continuous scientific research and industrial applications, the energy density of lithium-ion batteries using graphite as the negative electrode material is approaching the theoretical value (250 Wh / kg). -1 Currently, these technologies cannot meet the high energy density and high power density requirements of new energy vehicles and large-scale energy storage equipment.

[0003] Lithium metal anodes have a high theoretical specific capacity, up to 3860 mAh g. -1 The specific capacity of graphite lithium storage is 372 mAh g. -1 It is an order of magnitude higher than that of metal electrodes. At the same time, it has the lower potential of metal electrodes (-3.04V vs. RHE) and lower density (0.534g / cm³). -3 Lithium metal is considered the ideal anode material for next-generation batteries due to its advantages. However, because of its high chemical reactivity, the solid electrolyte interphase (SEI) film that spontaneously forms upon contact with organic electrolytes is fragile and cannot withstand the volume expansion associated with lithium metal deposition and stripping. Rupture of the SEI film exposes the internal lithium metal, leading to electrolyte consumption and low coulombic efficiency. Furthermore, ruptured SEI film easily becomes a site for lithium dendrite growth, which can eventually pierce the separator, reaching the positive electrode and causing a short circuit, thus posing safety risks.

[0004] To address the aforementioned problems of lithium metal anodes, researchers have conducted extensive studies focusing on electrolyte design, artificial SEI (Sediment-Insulated Electrode), and three-dimensional current collectors. The application of three-dimensional current collectors leverages their large specific surface area to effectively reduce local current density. Furthermore, their large internal space allows them to serve as a framework structure for lithium metal deposition. However, as good electron conductors, three-dimensional current collectors cannot suppress the reaction between electrons and the electrolyte when the SEI film ruptures, resulting in limited protection for the lithium metal. In research using three-dimensional current collectors as carriers for lithium metal deposition, combining the advantages of artificial SEI in regulating lithium metal deposition holds promise for the rational construction of high-performance, high-cycle-stability three-dimensional lithium metal current collectors. Summary of the Invention

[0005] According to one aspect of this application, a three-dimensional lithiophilic material is provided.

[0006] The three-dimensional lithiophilic material includes a substrate and a protective structural component;

[0007] The substrate is a carbonaceous substrate;

[0008] The carbon substrate is selected from at least one of carbon paper, carbon cloth, and carbon felt;

[0009] The protective structure components include Nb2O5 nanowires on a carbonaceous substrate.

[0010] Optionally, the total content of Nb2O5 in the material is 3-4 mg.

[0011] A second aspect of this application provides a method for preparing the above-mentioned three-dimensional lithiophilic material.

[0012] The method includes the following steps:

[0013] (1) Obtain a precursor solution containing a niobium source;

[0014] (2) The substrate is placed in the precursor solution and reacted to obtain the three-dimensional carrier-loving material.

[0015] Optionally, the niobium source in step (1) is selected from at least one of niobium oxalate and niobium pentachloride.

[0016] Optionally, the solvent in the solution described in step (1) is a mixture of water and ethanol; the volume ratio of water to ethanol in the mixture is any value or any two values ​​among 2:0.5, 2:0.7, 2:0.9, 2:1.1, 2:1.3, and 2:1.5.

[0017] Optionally, the solution described in step (1) may also contain hexamethylenetetramine.

[0018] Preferably, the ratio of the niobium source to hexamethylenetetramine is calculated using the molar number of niobium in the niobium source and the molar number of hexamethylenetetramine, and is any value among 2:2, 2:3, 2:4, 2:5, 2:6, 2:7, and 2:8, or a value between any two of these values.

[0019] Preferably, the ratio of the niobium source to hexamethylenetetramine is any value among 2:4, 2:5, and 2:6, or any value between any two of these ratios.

[0020] Preferably, the ratio of the niobium source to the solvent is calculated using the number of moles of niobium and the total volume of the solvent, and is any value among 1mol:10L, 1mol:11L, 1mol:12L, 1mol:13L, 1mol:14L, and 1mol:15L, or any value between any two of these.

[0021] Specifically, the preparation method of this three-dimensional carrier-loving material is as follows: the carbon paper three-dimensional current collector is ultrasonically cleaned in deionized water and anhydrous ethanol respectively, and then dried; niobium oxalate and hexamethylenetetramine are dissolved in a water / ethanol mixed solution, the heating temperature is controlled, and the mixture is stirred to obtain a uniform and transparent precursor solution; the obtained precursor solution and the carbon paper three-dimensional current collector are placed in a hydrothermal reactor, and the reaction temperature and time are controlled; the obtained Nb2O5 modified carbon paper current collector is taken out, repeatedly rinsed with deionized water and anhydrous ethanol, and then dried; the obtained Nb2O5 modified carbon paper current collector is calcined at high temperature in a tube furnace under an inert atmosphere.

[0022] The specific processing steps mentioned above also include cleaning the carbon paper three-dimensional current collector. The cleaning method is as follows: ultrasonically clean it in deionized water and anhydrous ethanol for 0.5 hours each, repeating 3 times, and drying it at 60°C.

[0023] In the specific processing steps described above, for Nb 5+ The precursor solution is prepared by heating the mixed solution to 60°C and stirring at this temperature at a speed of 500 rpm for 0.5-1 h.

[0024] Optionally, in step (2), the reaction temperature is any value or any two values ​​between 160, 165, 170, 175, 180, 185, 190, 195, and 200°C, and the reaction time is any value or any two values ​​between 10, 11, 12, 13, 14, and 15 h.

[0025] Preferably, the reaction temperature is any value among 175, 180, and 185°C or any value between any two points, and the reaction time is any value among 11, 12, and 13 hours or any value between any two points.

[0026] The preparation process described in this application includes a post-processing reaction after step (2). Specifically, after obtaining the Nb2O5-modified carbon paper, it needs to be washed, dried, and baked under inert gas conditions to remove any remaining organic matter. Specifically, washing involves rinsing three times each with deionized water and anhydrous ethanol, followed by drying at 60°C for 0.5-1 hour. Baking is performed using a tube furnace with an inert gas flow rate of 100 mL / min. -1 The heating rate is 3-4℃ / min. -1 The baking temperature is 700℃ and the baking time is 5 hours.

[0027] The three-dimensional lithiophilic material obtained using the above preparation method can successfully and uniformly coat Nb₂O₅ nanowires onto carbon fibers of carbon paper. This nanowire protective structure enhances carrier transport performance, forms active sites for lithium metal deposition, and enables uniform lithium metal deposition on the current collector, thereby improving the coulombic efficiency of the battery cycle. In comparison, carbon paper using Nb₂O₅-loaded materials exhibits better performance at 0.5 mA / cm². -2 Current density and 1 mA cm -2 At the deposition capacity, it can maintain a coulombic efficiency of 98.94% for 370 cycles, while ordinary carbon paper can only maintain a stable cycle of 150 cycles; at 4 mAcm -2 Current density and 2mAcm -2 At the deposition capacity, the Nb2O5-loaded carbon paper electrode can maintain a stable cycle of 600 cycles while maintaining a coulombic efficiency of 99.04%, which is far superior to the stable cycle of 100 cycles for the unloaded carbon paper.

[0028] A third aspect of the present invention provides the above-described materials and the materials obtained by the above-described methods as protective structural materials for the negative electrode of lithium metal batteries.

[0029] In a fourth aspect, the present invention provides a negative electrode material for a battery comprising the above-described material, the material obtained by the above-described method, and the negative electrode protection structure material described above.

[0030] A fifth aspect of the present invention provides a negative electrode material comprising the above-described material, a material obtained by the above-described method, and a negative electrode protection structure material comprising the above-described material, and a battery comprising the above-described negative electrode material;

[0031] The beneficial effects that this application can produce include:

[0032] 1) The three-dimensional lithiophilic material provided in this application has a large specific surface area, which can reduce the local current density during the lithium metal deposition and stripping process, suppress the growth of lithium dendrites, and achieve the safety and stability of battery cycling.

[0033] 2) The three-dimensional lithiophilic material provided in this application can be fully wetted with electrolyte, thereby improving the lithium ion transport performance, and can become an active site for lithium metal deposition, regulating the uniform deposition of lithium metal on the three-dimensional current collector, and improving the coulombic efficiency of battery cycle.

[0034] 3) The negative electrode of the battery provided in this application, at 4mAcm -2 Current density and 2mAcm -2 At the deposition capacity, the Nb2O5-loaded carbon paper electrode can maintain a stable cycling efficiency of 99.04% for 600 cycles; using it as a protective structure for the lithium metal anode, a high-capacity 5mAh cm⁻¹ electrode is also achieved. -2 Cathode LiNi 0.88Co 0.09 Al 0.03 O2-assembled full cells retain nearly 50% of their capacity after 160 cycles at a charge-discharge rate of 0.4C, demonstrating excellent commercialization prospects. Attached Figure Description

[0035] Figure 1 This is a scanning electron microscope image of the sample from Example 1.

[0036] Figure 2 The current density in Example 1 and Comparative Example 1 is 0.5 mA cm⁻¹. -2 The deposition surface capacity is 1 mAh cm⁻¹ -2 Half-cell coulombic efficiency test under certain conditions.

[0037] Figure 3 The current density in Example 1 and Comparative Example 1 is 2 mA cm⁻¹ -2 The deposition surface capacity is 1 mAh cm⁻¹ -2 Half-cell coulombic efficiency test under certain conditions.

[0038] Figure 4 The cycle performance of the full cells in Example 1 and Comparative Example 1 at 0.4C was tested. Detailed Implementation

[0039] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0040] Unless otherwise specified, all raw materials used in the embodiments of this application were purchased through commercial channels.

[0041] The assembly processes for the half-cell and full-cell in the following embodiments are as follows: The half-cell assembly uses a CR2032 coin cell device; the battery separator uses a commercially available Celgard 2320 model separator; the half-cell assembly uses a 16mm diameter, 200μm thick lithium metal disc as the negative electrode, and the full-cell assembly uses a 16mm diameter, 50μm thick lithium metal disc as the negative electrode; the half-cell assembly uses a 16mm diameter carbon paper current collector obtained in the comparative example and the embodiment as the positive electrode, and the full-cell assembly uses a 14mm diameter high-load (5mAh cm⁻¹) current collector. -2 LiNi 0.88 Co 0.09 Al 0.03 O2 positive electrode. The assembly structure from bottom to top consists of positive electrode shell, positive electrode, separator, lithium metal negative electrode, gasket, spring contact, and negative electrode shell. The organic electrolyte used in the battery assembly process is a carbonate-based electrolyte, and the solvents used are ethylene carbonate (EC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC). In the following examples, the electrolyte used is LiPF6 dissolved in EC and DEC (volume ratio 1:1) at a concentration of 1 mol / L.-1 Add 5 vol% FEC. For full cell assembly, place the carbon paper current collector obtained in the comparative example and the embodiment below as a protective structure between the separator and the lithium metal anode. The assembly process must be carried out in a glove box filled with 99.999% argon, and the moisture and oxygen content of the glove box must be controlled below 0.1 ppm.

[0042] In the following embodiments, the testing conditions for half-cell and full-cell tests using the Blue Charge testing system are as follows: At room temperature, the battery is placed in the alligator clips of the Blue Charge testing device. Half-cell test procedure: After standing for 2 hours, a 0.5 mA cm⁻¹ test is performed. -2 or 2mAcm -2 The battery was discharged at the same current density until the voltage reached 0V, then discharged for another 30 minutes at the same current density, and then charged at the same current density until the lithium metal stripping cutoff voltage of 1V was reached, completing one charge-discharge cycle. This process was repeated until the battery coulombic efficiency decreased to 50%, at which point the program ended. Full battery test procedure: resting time of 12 hours, charge-discharge cutoff voltage of 2.8-4.3V vs. Li / Li + First, the battery is pre-cycled for 6 weeks at a charge / discharge rate of 0.1C. Then, a full-cell cycle stability test is performed at a charge / discharge rate of 0.4C until the capacity retention rate is below 50% or the coulombic efficiency fluctuates unstablely, at which point the program ends.

[0043] Example 1

[0044] (1) Weigh 0.002 mol niobate oxalate and 0.0005 mol hexamethylenetetramine and add them to 30 mL of a water / anhydrous ethanol mixture (volume ratio 2:1). Place the mixture on a stirring and heating table and heat and stir at 60 °C until the solution becomes colorless and transparent to obtain the precursor solution.

[0045] (2) Transfer the precursor solution prepared in step 2 to a hydrothermal reactor, and place the carbon paper current collector obtained in Comparative Example 1 at the bottom of the hydrothermal reactor. Then place the hydrothermal reactor in a forced-air drying oven and keep it at 180°C for 12 hours. The obtained material is rinsed three times each with deionized water and anhydrous ethanol, and then transferred to a forced-air drying oven to dry at 60°C.

[0046] (3) The obtained material was tested in a tube furnace under 100 mL / min inert argon atmosphere. -1 At a gas flow rate of 3-4℃ / min -1 The temperature was increased to 700℃ at a certain rate and held for 5 hours to obtain a three-dimensional current collector for Nb2O5-modified carbon paper.

[0047] The scanning electron microscope image of the obtained Nb2O5 modified carbon paper three-dimensional current collector is shown below. Figure 4As shown, Nb2O5 nanowires can be uniformly wrapped around the surface of carbon fibers.

[0048] Example 2

[0049] Figure 1-2 The current density and areal capacitance are 0.5 mA cm⁻¹, respectively. -2 1mAh cm -2 ;2mA cm -2 1mAh cm -2 The cyclic coulombic efficiency plot shows that, under different current density conditions, the Nb2O5-modified carbon paper current collector exhibits better cycling stability at high current densities compared to the unmodified carbon paper current collector.

[0050] Example 3

[0051] Figure 3 The graph shows the cycle capacity efficiency of a full cell using unmodified carbon paper current collectors and Nb2O5-modified carbon paper current collectors as lithium metal anode protective layers. At a relatively high charge / discharge rate (0.4C), the Nb2O5-modified carbon paper current collector provides better protection for the lithium metal. It also exhibits a longer cycle life with limited lithium sources.

[0052] Comparative Example 1

[0053] Prepare a carbon paper current collector according to the following steps.

[0054] (1) The carbon paper current collector with a diameter of 16 mm was ultrasonically cleaned in deionized water and anhydrous ethanol for 0.5 h each time, and repeated 3 times. Then it was placed in a forced-air drying oven and dried at 60 °C to obtain a clean carbon paper current collector. The current collector was used as a control example for testing.

[0055] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A lithium metal battery negative electrode protection structure material, characterized in that, The lithium metal battery negative electrode protection structure material includes a three-dimensional lithiophilic material; The three-dimensional lithiophilic material includes a substrate and a protective structural component; The substrate is a carbonaceous substrate; The carbon substrate is selected from at least one of carbon paper, carbon cloth, and carbon felt; The protective structure components include Nb2O5 nanowires on a carbonaceous substrate; The Nb2O5 nanowires are obtained by reacting the substrate and a precursor solution containing niobium source in a hydrothermal reactor to uniformly coat the carbon fiber surface of the carbonaceous substrate.

2. The lithium metal battery negative electrode protection structure material according to claim 1, characterized in that, The total content of Nb2O5 in the material is 3-4 mg.

3. A method for preparing the lithium metal battery negative electrode protective structure material according to any one of claims 1 or 2, characterized in that, Includes the following steps: (1) A precursor solution containing a niobium source was obtained; (2) The substrate and precursor solution are placed in a hydrothermal reactor and reacted to obtain the three-dimensional lithiophilic material.

4. The method according to claim 3, characterized in that, The niobium source mentioned in step (1) is selected from at least one of niobium oxalate and niobium pentachloride.

5. The method according to claim 3, characterized in that, The solution described in step (1) is a mixture of water and ethanol as the solvent. In the mixture, the volume ratio of water to ethanol is 2:(0.5-1.5).

6. The method according to claim 3, characterized in that, The solution described in step (1) also contains hexamethylenetetramine; The ratio of the niobium source to hexamethylenetetramine is calculated using the molar number of niobium in the niobium source and the molar number of hexamethylenetetramine, and is 2:(2-8).

7. The method according to claim 6, characterized in that, In step (1), the ratio of the niobium source to hexamethylenetetramine is 2: (4-6).

8. The method according to claim 3, characterized in that, In step (1), the ratio of niobium source to solvent is calculated using the moles of niobium and the total volume of solvent, which is 1 mol: (10-20) L.

9. The method according to claim 3, characterized in that, In step (1), the ratio of the niobium source to the solvent is 1 mol: (14-16) L.

10. The method according to claim 3, characterized in that, The reaction described in step (2) is carried out at a temperature of 160-200℃ for 10-15 hours.

11. The method according to claim 3, characterized in that, The reaction described in step (2) is carried out at a temperature of 175-185℃ for 11-13 hours.

12. A battery, characterized in that, The battery includes the lithium metal battery negative electrode protection structure material as described in claim 1 or 2, or includes the lithium metal battery negative electrode protection structure material prepared by the method described in any one of claims 3-11.

Citation Information

Patent Citations

  • Composite 3D current collector and preparation and application thereof

    CN109873162A